The role of glutathione transferase polymorphisms in the development of diabetic nephropathy - Dragana Tošović Pavlović; Siniša Ristić (Биомедицинска истраживања, 2021)
Genetic and environmental factors play an important role in the development of type 2 diabetes mellitus (DM2) and its complications. Diabetic nephropathy (DN) is one of the most common microangiopathic chronic complications of diabetes. Oxidative stress occurs under condition of increased production of free radicals and/or decreased activity of antioxidant defense mechanisms and it is an important link in the complex mechanism of diabetic vascular changes. Glutathione transferases (GST) are enzymes involved in xenobiotic metabolism and they are part of complex antioxidant defense mechanisms. Numerous studies have found an association of GST gene polymorphism to a predisposition to various diseases, including diabetes and diabetic nephropathy. Our and other authors' results suggest that genetic variations in enzymes involved in free radical metabolism are associated with the development of end-stage kidney disease in patients with diabetes, which could become the basis for the development of preventive and early therapeutic strategies in high risk people.
Keywords: diabetes; diabetic nephropathy; glutathione transferase polymorphism